Small and large oscillatory shear properties of concentrated proteins. (January 2021) - Schreuders, F.K.G.; Sagis, L.M.C.; Bodnár, I.; Erni, P.; Boom, R.M.; van der Goot, A.J.
Abstract: A closed cavity rheometer was employed to assess the properties of concentrated protein materials before, during and after thermal treatment, using conditions that are relevant to the production of meat analogues. Pea and soy protein isolate and wheat gluten were used as model matrices. The analysis was done using Lissajous curves, both for small and large amplitude oscillatory shear deformation. The energy dissipation ratios based on the enclosed area inside the Lissajous curves characterize the plasticity of the materials. The results show that the modulus of wheat gluten increases during heating and remains elevated after cooling. In contrast, the moduli of pea and soy protein isolates decrease during heating. Subsequent cooling leads to properties that are similar to the rheological properties of unheated pea and soy protein isolates. Lissajous curves and energy dissipation ratios provide insight in the non-linear response. At 30 °C, pea and soy protein isolate have a higher dissipation ratio than wheat gluten. Upon a heat treatment and even after cooling, the dissipation ratio was smaller at similar strain amplitude compared with 30 °C. This indicates that heating induced more elasticity. Upon heating, pea protein isolate loses its elastic properties faster than soy protein isolate, while wheat gluten showed abrupt dissipation after extensive deformation. The observed characteristics are consistent with the behaviour during extrusion and shearing, in which wheat gluten forms extended filaments, while soy and pea protein isolates form a homogeneous matrix. Studying the large oscillatory shear behaviour during and after thermal treatment provides a more detailed picture of the rheological changes during processing, than one would obtain through classical rheology. The dissipation ratio summarizes the information in the Lissajous curves. These insights help to better identify material-structure-process relationships for concentrated plant protein materials during thermomechanical conversions, such as extrusion. Graphical abstract: Image 1 Highlights: Non-linear shear behaviour was analysed with a closed cavity rheometer and interpreted using Lissajous curves. The influence of processing conditions was investigated using small and large amplitude oscillatory shear deformation. The energy dissipation ratio reveals the complex information in the Lissajous curves in a compact manner. The type of protein, its thermal history and strain determine the elasticity and dissipation ratio to the greatest extent.